Reconstruction of the Epistemology of Mathematics Education: Integration of the Rationality of the Philosophy of Science and the Emotional Psychology of Students - Aisyah Nursyam; Abdullah Sinring; Syamsu Kamaruddin; Muhammad Rizal Usman (Juring (Journal for Research in Mathematics Learning), 2025)
This study aims to reconstruct the epistemology of mathematics education by integrating the philosophy of science and students’ emotional psychology. The epistemological crisis in mathematics learning is characterized by the dominance of rationalistic approaches that tend to ignore students' affective and reflective dimensions. Empirical evidence indicates a high level of mathematics anxiety and low emotional engagement, both of which affect students’ motivation and academic performance. This research employs a Systematic Literature Review (SLR) method based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol by analyzing 45 national and international articles published between 2012 and 2025. Data were analyzed thematically through three stages: conceptual coding, thematic classification, and interpretative synthesis. The review identifies four main themes: (1) epistemology of mathematics education and the philosophy of science, (2) emotional intelligence and self-reflection, (3) mathematics anxiety and affective resilience, and (4) learning motivation and academic achievement. The integration of the philosophy of science reorganizes rationality in mathematics education to be more reflective and humanistic, while emotional psychology balances cognition and affection. The conceptual model positions the epistemology of mathematics education as the core, interacting dynamically with emotional intelligence, mathematics anxiety, and learning motivation that together influence students’ academic performance. The findings emphasize the need to reconstruct the epistemology of mathematics education toward a balance between rationality and emotional awareness. Accordingly, mathematics learning should be developed through reflective, humanistic, and experience-based approaches to foster students as epistemic subjects who think rationally and mature emotionally.